Irruzione del cinema, evasione del teatro. Franz Castorf mette in scena Umiliati e offesi di Dostoevskij - Haß, Ulrike (Kritik. Rivista di letteratura e critica culturale, 2024)
This essay discusses Castorf’s theater. His plays are taken from Dostoevsky’s novels and are based precisely on the moment of the turning point in mediality. Between 1999 and 2003, Castorf is not at all interested in trying to address a present full of catastrophes with a paraphrase of Dostoevsky. Rather he, in a precise and congenial movement, welcomes Dostoyevsky’s writing into the center of his work and repeats in the sphere of theater “the effort of the form that counteracts itself” that is made in the Russian writer’s novels.